Functional muscle mechanics in sports: why we should care! - Herzog, W.; Killick, A. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The mechanical properties of muscles frequently determine the performance limits of athletes. Nevertheless, even the most basic properties of muscles, such as the force-length and force-velocity relationships are rarely considered in sport performance analysis. Here, we demonstrate with examples of track cycling and cross-country skiing that many technical choices in sport can be explained by an understanding of the basic properties of skeletal muscles and that performance can be enhanced as a result of this understanding. There is a gap of research between sport and muscle mechanics that is largely unexplored but offers exciting possibilities for basic science and applied athletic coaching and training.